The origins and dispersal throughout the Pacific Islands of Fehi bananas (Musa series Australimusa) - Thomson, Lex J.; Butaud, Jean-François; Daniells, Jeff; Geraghty, Paul A.; Hariej, Adriana; Kagy, Valérie; Kennedy, Jean; Keppler, Angela K.; Mabberley, David J.; Sachter-Smith, Gabriel L.; Sardos, Julie; Wilson, William H.; et al. (Polynesian Society, 2022)
Fehi bananas are a Pacific Islands and eastern Indonesian assemblage of parthenocarpic diploid and triploid cultivars in Musa series Australimusa. Fehi cultivars were derived principally from M. maclayi, M. lolodensis and M. bukensiss.l. and related entities. Eleven Fehi cultivar groups comprising morphologically similar cultivars are described, along with naturalised forms from eastern Polynesia. Fehi cultivars have been referred to particular species such as M. troglodytarum and M.fehi, but further genetic research is needed to ascertain how human-selected cultivars are interrelated and derived from any particular species.